Efecto de un programa tutorial en el mejoramiento de la autoestima en estudiantes de quinto grado de secundaria en la Institución Educativa Felipe Ramón Documet Silva, Nauta 2022 - Garcia Rojas, Milagros de Jesus (2023)
The objective of the study was to apply a tutorial program to verify its effect on the improvement of self-esteem in students of the fifth grade of secondary school Felipe Ramón Documet Silva, Nauta - 2022. It is an evaluative research of quasi-experimental design. The population was 120 students and an intentional sample of 120 students (53 students from the experimental group and 67 from the control group), a test was used to identify self-esteem. The study concludes by stating that the students who participated in the tutorial program significantly improved their self-esteem than those who did not participate in said program, therefore the general hypothesis formulated is approved (p-value =0.000 <0.05). It was determined that the application of the tutorial program significantly improves self-esteem in the Ego, Social-partners, and Academic dimensions in the student subjects of the sample, for which specific hypotheses 1, 2, and 3 formulated (p-value =0.000 <0.05).